A REVIEW OF RESEARCH STUDIES ON THE VARIOUS EXPECTATIONS OF STUDENTS, PARENTS AND TEACHERS FROM PRIVATE UNIVERSITIES - 1. Anusha Arif , 2. Dr. Vivek Rogers (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Private Universities globally are entrusted with the responsibility of providing high-quality education and fostering conducive learning environments. However, meeting the diverse Expectations of Students, Parents, and Teachers, poses significant challenges to these Universities. The Expectations of Students from Private Universities encompass various dimensions, including academic quality, infrastructure, career opportunities, financial transparency, and support services. Students expect high-quality education delivered by competent faculty members, modern facilities, access to career guidance and placement services, transparent fee structures, and efficient support systems to address academic and personal needs. Research studies have highlighted the importance of these factors in shaping student satisfaction and retention in Private Universities. Parents have their own set of Expectations from Private Universities, often influenced by concerns about their children’s academic and career success. They prioritize academic reputation, infrastructure, placement opportunities, financial transparency, and communication channels with the Private Universities. Research studies emphasize the significance of parental involvement and satisfaction in the decision-making process regarding their children’s education and the role of Private Universities in meeting these Expectations to build trust and long-term relationships. Teachers, in Private Universities, have Expectations related to academic freedom, supportive work environments, fair compensation, professional growth opportunities, and transparent governance. Research studies have identified challenges such as faculty recruitment and retention, communication gaps, regulatory compliance burdens, and resource limitations that hinder Private Universities’ ability to meet these expectations. Addressing these challenges is crucial for attracting and retaining competent faculty members and maintaining teaching quality and research output. This paper provides a comprehensive review of the Expectations held by Students, Parents, and Teachers from Private Universities by understanding and addressing their diverse Expectations. By prioritizing student success, fostering collaboration, and supporting teachers, private universities can create an environment where everyone can thrive and reach their full potential. Working together, students, parents, and teachers can ensure that private universities fulfil their promise of providing a transformative educational experience for all.